Cartilage oligomeric matrix protein and hyaluronic acid are sensitive serum biomarkers for early cartilage lesions in the knee joint. (17th February 2016) - Jiao, Qiang; Wei, Lei; Chen, Chongwei; Li, Pengcui; Wang, Xiaohu; Li, Yongping; Guo, Li; Zhang, Congming; Wei, Xiaochun
Abstract: The purpose of this study was to evaluate the relationship between five previously established serum osteoarthritis biomarkers and the severity of cartilage lesions in the knee. Cartilage damage (classified according to the Outerbridge scoring system) and serum concentrations of cartilage oligomeric matrix protein (COMP), collagen type II C-telopeptide (CTX-II), matrix metalloproteinase-3 (MMP-3), collagen type III N-propeptide, (PIIINP), and hyaluronic acid (HA) were determined in 79 patients who underwent knee arthroscopy or total knee replacement. HA and COMP concentrations were significantly higher in the Outerbridge score 1 and 2 groups, respectively. These results suggest that serum COMP and HA concentrations can be used to predict early cartilage lesions in the knee.